Um programa para o cálculo automático estático e dinâmico de sistemas de tubulações - Araújo, Ézio da Rocha (1978)
It is presented a computer program for static and dynamic analysis of linear piping systems. Some special elements are developed to represent straight and curved pipe, and rigid components as well. It is possible to include in the analysis: mitre bends, valves, flanges, expansion joints and elastic restraints, among others components. Several types of loading may be considered simultaneously in the static analysis: gravity loads, thermal expansion and anchor movements, internal pressure, and others sustained mechanical loads. The dynamic analysis is deterministic, with particular emphasis on nuclear power piping, principally seismic response-spectra and time history. The governing movement equations are transformed on normal coordinates and the solution is performed by step-by-step integration techniques. Discret or consistent mass matrices for straight and circularly curved pipe are utilized in the analysis. A complete listing in FORTRAN language for a Burroughs B/6700 computer is included in the Appendix.